2016
DOI: 10.11301/jsfe.17.33
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Plant-Based Agricultural Waste by Subcritical Water Treatment

Abstract: The application of subcritical water treatments to valorize cer tain plant-based agricultural waste is reviewed with a focus on the extraction of phenolic compounds and the production of oligosaccharides. Phenolic compounds can be ef ficiently extracted by raising the temperature to an optimal value; however, many phenolic compounds are decomposed at high temperatures. Nevertheless, some degradation products of phenolic compounds also show high antioxidant activity. The conversion of polysaccharides from plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In this case, the temperature is more important than pressure to promote the depolymerization of the polysaccharides and favor their solubility due to the reduction of their molecular weight. The range of temperatures for recovery of polysaccharides vary between 120 to 250 o C depending on the type and source of biomass [47], while pressure is kept around 10 MPa when dealing with SWE.…”
Section: Green Extraction Techniques For Obtaining Antiviral and Anti-inflammatory Compoundsmentioning
confidence: 99%
“…In this case, the temperature is more important than pressure to promote the depolymerization of the polysaccharides and favor their solubility due to the reduction of their molecular weight. The range of temperatures for recovery of polysaccharides vary between 120 to 250 o C depending on the type and source of biomass [47], while pressure is kept around 10 MPa when dealing with SWE.…”
Section: Green Extraction Techniques For Obtaining Antiviral and Anti-inflammatory Compoundsmentioning
confidence: 99%
“…Subcritical water is defined as hot water at a temperature ranging between 100 and 374°C under high pressure to maintain water in the liquid state (Pourali, Asghari, & Yoshida, ). Subcritical water has been widely used for extraction, hydrolysis, and conversion of carbohydrates in low‐value biomass into useful compounds (Khuwijitjaru, ). Khuwijitjaru, Watsanit, and Adachi () used subcritical water treatment to hydrolyze polysaccharide from coconut meal to obtain a manno‐oligosaccharide and found that high extraction temperature (230°C) and short treatment time (<3 min) tended to provide high amounts of carbohydrate with greater mannose contents.…”
Section: Introductionmentioning
confidence: 99%